2007
DOI: 10.1007/s11049-006-9010-9
|View full text |Cite
|
Sign up to set email alerts
|

The Object Agreement Constraint

Abstract: This paper is an extensively revised and expanded version of the first part of a broader paper that was circulated as Ormazabal & Romero (2002) and also included a syntactic analysis of the agreement restrictions discussed here. The syntactic proposal analyzed the properties of a series of ditransitive constructions that were shown to be subject to the restriction: dative Constructions, dative Clitic Constructions and Double Object Constructions, all in a broad variety of languages. Due to editorial requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 32 publications
(33 reference statements)
1
47
0
Order By: Relevance
“…In previous work (Ormazabal and Romero 2007, 2013a, 2013b we have argued that some objects do not require any formal licensing -they do not enter into an agreement relation or receive Case-, while others must establish a formal relation with the verb. The kind of objects that belong to one group or the other is not arbitrary, but it is parametrically determined.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In previous work (Ormazabal and Romero 2007, 2013a, 2013b we have argued that some objects do not require any formal licensing -they do not enter into an agreement relation or receive Case-, while others must establish a formal relation with the verb. The kind of objects that belong to one group or the other is not arbitrary, but it is parametrically determined.…”
Section: Introductionmentioning
confidence: 87%
“…This «activation» may be due to the fact that P cannot morphologically encode agreement. Ormazabal and Romero (2007) observe that those languages where P can represent agreement, as Celtic languages, lack Doble Object Construction.…”
Section: On Cliticizationmentioning
confidence: 96%
“…In MOCs, only one of the objects can receive structural Case; the other gets non-structural Case. Ormazabal & Romero (2007) call this the Object Agreement Constraint (OAC), which I will adopt. The definition of OAC is given in (5): (10) Object Agreement Constraint (OAC)…”
Section: A Case Competition Approachmentioning
confidence: 99%
“…person) cannot be checked twice. As expected, the PCC issue never arises when two DPs check their features in different projections (=30a) but is at stake in some well-known cases (=30b): (30) (Ormazabal & Romero 2007: 316) In examples like (30a), no conflict arises given the standard assumption that subjects and objects check their case and φ-features against different functional heads (T and v); examples like (30b), on the other hand, are usually referred to as violations of Bonet's Person-Case Constraint: (31) Person-Case Constraint if DATIVE, then ACC/ABS = 3 rd person (Bonet 1994: 36) This constraint is under scrutiny in current theory: Ormazabal and Romero (2007) have convincingly shown that the constraint is basically syntactic in nature, independent of case and morphological realization, and propose to derive it from the impossibility of having two animate objects agreeing with the verbal complex. Since we don't deal with object agreement proper but with a configuration where subject and object check the same feature, more abstract approaches seem relevant: Boeckx (2003) and, specially, Jeong (2004 argue that in situations of multiple feature checking, multiple case checking is licit given that case is an uninterpretable feature on the goal (and can be checked in a symmetric way); multiple person checking is, however, illicit since it is only interpretable on the goal and dependent on asymmetric checking (closest ccommand) which can only take place once.…”
Section: Pcc Effects As Evidence For Multiple Checkingmentioning
confidence: 99%